The effects of different lipid emulsions on the lipid profile, fatty acid composition, and antioxidant capacity of preterm infants: A double-blind, randomized clinical trial. Issue 5 (October 2016) - Wang, Ying; Feng, Yi; Lu, Li-Na; Wang, Wei-Ping; He, Zhen-Juan; Xie, Li-Juan; Hong, Li; Tang, Qing-Ya; Cai, Wei
Summary: Background & aims: Olive oil (OO), medium-chain triglycerides (MCT)/long-chain triglycerides (LCT) mixture and soybean oil (SO) lipid emulsions are currently used for preterm infants in China. The aim of our study was to compare the lipid profile, fatty acid composition, and antioxidant capacity of preterm infants administered OO, MCT/LCT, or SO lipid emulsions. Methods: In this study, 156 preterm infants (birth weight < 2000 g and gestational age < 37 weeks) received parenteral nutrition (PN) containing OO, MCT/LCT, or SO lipid emulsions for a minimum of 14 d. On days 0, 7, and 14, the lipid profile, fatty acid composition and antioxidant capacity were analyzed. Results: On day 7, HDL levels in the MCT/LCT group were significantly lower than in the OO (1.06 ± 0.40 mmol/L) or SO groups. LDL levels were higher in the OO group than in the MCT/LCT or SO groups on day 7. A-I/B was higher in MCT/LCT than in OO or SO groups. Myristic acid (C14:0) levels on days 7 and 14 increased in MCT/LCT compared to the OO and SO groups. The OO group had higher oleic acid (C18:1n9) levels than the two other groups. Linoleic acid (C18:2n6), linolenic acid (C18:3n3), and eicosapentaenoic acid (20:5n3) were significantly lower in the OO group than in MCT/LCT or SO groups. Monounsaturated fatty acid levels decreased, and ω-6 polyunsaturated fatty acid and essential fatty acids levels increased in MCT/LCT and SO groups. No significant differences were obtained in SOD, MDA, GSH-Px, and T-AOC among the groups. Conclusion: The three lipid emulsions were safe and well tolerated in preterm infants. Oleic acid (C18:1n9) levels increased and LA (C18:2n6), ALA (C18:3n3), and EPA (C20:5n23) levels decreased in OO compared to MCT/LCT or SO. Clinical trial registration number:NCT01683162, https://register.clinicaltrials.gov/ .